Development of synbiotic ice cream from goat milk - Robins, Ajisha; Radha, K (Indian Journal of Dairy Science, 2020)
Synbiotic ice cream was developed from goat milk by using inulin as a prebiotic and Lactobacillus plantarum (UBLP-40) as a probiotic. The treatment mix was formulated to contain more than 10% fat, 8.6% milk solids not fat, 2% inulin, 15% sugar, 0.4% stabilizer-emulsifier combination and Â probiotic Lactobacillus plantarum culture. Physico-chemical, microbiological and sensory qualities of control and synbiotic ice cream were compared. Synbiotic ice cream showed higher whipping ability (p<0.05) than control. Synbiotic ice cream was superior in sensory qualities than control during 30 days of storage. There was no significant difference in fat, protein, meltdown time and weight per litre.